Brood size influences patterns of DNA methylation in wild Zebra Finches (Taeniopygia guttata). (19th September 2018) - Sheldon, Elizabeth L.; Schrey, Aaron W.; Ragsdale, Alexandria K.; Griffith, Simon C.
Abstract: Both natural and experimentally manipulated brood size can influence the competition dynamics among siblings in a nest and alter the environment during early development in birds. Brood size affects a variety of life-history and fitness-related traits, but relatively little is known about the mechanisms that might mediate these effects. There is accumulating evidence that early-life environments can influence adult phenotypes though epigenetic mechanisms such as variation in DNA methylation. Here, we profile DNA methylation in nestling Zebra Finches ( Taeniopygia guttata ) raised in naturally variable and experimentally manipulated brood sizes. We found that (1) natal brood size is significantly, positively correlated with percent DNA methylation in blood; and (2) individuals in manipulated broods experience significantly more demethylation events across early development than individuals from broods that remain the same size. Any manipulation of brood size creates fluctuations in early developmental conditions, potentially explaining why the frequency of demethylation events in these treatments was higher than in control broods. We also found that the specific loci that lost and gained methylation across early development differed between individuals in enlarged and reduced broods, which may reflect the different developmental pressures imposed by the different manipulations. Although the phenotypic consequences of reduced levels of methylation are yet to be elucidated, our findings support the hypothesis that brood size is associated with the prevalence and pattern of DNA methylation in wild birds.